Proceedings of the 2nd Workshop on Coreference Resolution Beyond OntoNotes (CORBON 2017) 2017
DOI: 10.18653/v1/w17-1508
|View full text |Cite
|
Sign up to set email alerts
|

Projection-based Coreference Resolution Using Deep Syntax

Abstract: The paper describes the system for coreference resolution in German and Russian, trained exclusively on coreference relations projected through a parallel corpus from English. The resolver operates on the level of deep syntax and makes use of multiple specialized models. It achieves 32 and 22 points in terms of CoNLL score for Russian and German, respectively. Analysis of the evaluation results show that the resolver for Russian is able to preserve 66% of the English resolver's quality in terms of CoNLL score.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Martins [98] applied projection on an English-Portuguese-Spanish parallel corpus, reporting strong results compared with other cross-lingual methods, such as bilingual word embeddings, bitext direct projection, or vanilla posterior regularization. For the same goal, Novák et al [99] reported improved cross-lingual results on the CORBON 2017 shared task [36], building German and Russian coreference resolvers based solely on parallel English data.…”
Section: Cross-lingual Coreference Resolutionmentioning
confidence: 98%
See 2 more Smart Citations
“…Martins [98] applied projection on an English-Portuguese-Spanish parallel corpus, reporting strong results compared with other cross-lingual methods, such as bilingual word embeddings, bitext direct projection, or vanilla posterior regularization. For the same goal, Novák et al [99] reported improved cross-lingual results on the CORBON 2017 shared task [36], building German and Russian coreference resolvers based solely on parallel English data.…”
Section: Cross-lingual Coreference Resolutionmentioning
confidence: 98%
“…Cross-lingual knowledge transfer generally relies on either a common multi-lingual semantic space [49,96,97] or on parallel corpora, which enables projection of information from one language to another [98,99]. The use of multilingual word embeddings [49] as a multi-lingual semantic space enables the use of direct transfer learning between languages [100].…”
Section: Cross-lingual Coreference Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been used to create a coreference resolver by multiple authors, e.g. de Souza andOrȃsan (2011), Martins (2015), Wallin and Nugues (2017), and Novák et al (2017). However, since the present work employs the corpus-based approach on gold annotations of coreference, we offer more details on works of Postolache et al (2006) and Grishina andStede (2015, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…This approach has been used to create a coreference resolver by multiple authors, e.g. de Souza and Orȃsan (2011), Martins (2015), Wallin and Nugues (2017), and Novák et al (2017). However, since the present work employs the corpus-based approach on gold annotations of coreference, we offer more details on works of and Stede (2015, 2017).…”
Section: Related Workmentioning
confidence: 99%